2000
DOI: 10.1002/1521-3935(20000801)201:12<1226::aid-macp1226>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and mathematical modeling of molecular weight and chemical composition distributions of ethylene/-olefin copolymers synthesized with a heterogeneous Ziegler-Natta catalyst

Abstract: The distributions of molecular weight and chemical composition of two linear low‐density polyethylene resins synthesized with Ziegler‐Natta catalysts were analyzed with several microstructural characterization techniques and the results were used to investigate the nature of the active site types present on the catalyst. Deconvolution of the molecular weight distribution measured by gel permeation chromatography and of the chemical composition distribution measured by either crystallization analysis fractionat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
64
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 8 publications
2
64
0
Order By: Relevance
“…[ 1,2 ] Furthermore, the CCD can also be used to investigate the nature of multiple-site-type catalysts and the effect a single-site-type catalyst; therefore, the distributions of molecular weight and chemical composition are narrow and unimodal, and MWD polydispersity is close to 2.0. The sample had 1.86 mol% of 1-octene and a number-average molecular weight (M n ) of 31 600 g mol −1 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 1,2 ] Furthermore, the CCD can also be used to investigate the nature of multiple-site-type catalysts and the effect a single-site-type catalyst; therefore, the distributions of molecular weight and chemical composition are narrow and unimodal, and MWD polydispersity is close to 2.0. The sample had 1.86 mol% of 1-octene and a number-average molecular weight (M n ) of 31 600 g mol −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, the deconvolution of any weight distribution function (Equation 5–8) should identify the same number of site types and yield the same set of mass fractions and kinetic parameters for each site type. However, independent deconvolutions of MWD and CCD were reported to lead to a different number of site types and slightly different set of mass fractions and kinetic parameters 19. Differences in site type number are expected, as some site types may produce chains with similar average molecular weights but different comonomer contents, or vice versa .…”
Section: Deconvolution Of Microstructural Characteristicsmentioning
confidence: 99%
“…The termination criterion is that when the number of site types increase, the value of the objective function increased, stopped decreasing, or did not decrease significantly. This criterion is commonly used for the deconvolution of microstructural properties distributions 9, 11, 12, 19, 20, 23–25 …”
Section: Deconvolution Of Microstructural Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kissin and others have found that five to seven Flory components are often needed to adequately match the MWD of polyolefins produced using Ziegler‐Natta catalysts 4,10,12,13. However, it is widely believed that there are not this many chemically distinct types of active sites on Ziegler‐Natta catalysts.…”
Section: Introductionmentioning
confidence: 99%